220k views
4 votes
What is the answer to this

What is the answer to this-example-1
User Jbmyid
by
5.4k points

2 Answers

0 votes

Answer:


\displaystyle (1)/(36)

Explanation:

According to the Product-to-Power Exponential Rule, whenever you multiply similar bases, you keep the base and add the exponents:


\displaystyle [-6]^(-2) = [-6]^(-10) * [-6]^8 → (1)/(36) = [-6]^(-2)

I am joyous to assist you anytime.

User Lamp Ard
by
4.6k points
7 votes

Answer:

(-6)^-10 · (-6)^8 = (-6)^(-10+8)= (-6)^-2

User Legenddaniel
by
5.3k points